(untitled) (Argos, 2025)
The literary critics calls Claudius Claudianus (370 AD?-410 AD) "the last poet of classic Rome"; this denomination, which excludes late Ancient Time, supports as a literary paradigm the recreation of the epic form without understanding that Claudianus reproduces poetically a dissimilar perspective regarding the ephemeral imperial Classicism. In Rufinum, it is the product of a relationship between the poet and Honorio’s court, where general Estilicon developed his power after Teodosio’s death in the year 395. The antinomy with which Claudiano represents the "masters" of Occident’s opposition with the monstrous Rufinus, is based on the handle of a rhetoric plethoric of baroques and the deepening of client state that has in the panegyric its generic reproduction.